An ionizing radiation acoustic imaging (iRAI) technique for real‐time dosimetric measurements for FLASH radiotherapy. Issue 10 (16th August 2020) - Oraiqat, Ibrahim; Zhang, Wei; Litzenberg, Dale; Lam, Kwok; Ba Sunbul, Noora; Moran, Jean; Cuneo, Kyle; Carson, Paul; Wang, Xueding; El Naqa, Issam
Abstract : Purpose: FLASH radiotherapy (FLASH‐RT) is a novel irradiation modality with ultra‐high dose rates (>40 Gy/s) that have shown tremendous promise for its ability to enhance normal tissue sparing while maintaining comparable tumor cell eradication toconventional radiotherapy (CONV‐RT). Due to its extremely high dose rates, clinical translation of FLASH‐RT is hampered by risky delivery and current limitations in dosimetric devices, which cannot accurately measure, in real time, dose at deeper tissue. This work aims to investigate ionizing radiation acoustic imaging (iRAI) as a promising image‐guidance modality for real‐time deep tissue dose measurements during FLASH‐RT. The underlying hypothesis is that iRAI can enable mapping of dose deposition with respect to surrounding tissue with a single linear accelerator (linac) pulse precision in real time. In this work, the relationship between iRAI signal response and deposited dose was investigated as well as the feasibility of using a proof‐of‐concept dual‐modality imaging system of ultrasound and iRAI for treatment beam co‐localization with respect to underlying anatomy. Methods: Two experimental setups were used to study the feasibility of iRAI for FLASH‐RT using 6 MeV electrons from a modified Varian Clinac. First, experiments were conducted using a single element focused transducer to take a series of point measurements in a gelatin phantom, which was compared with independent dose measurements using GAFchromic film. Secondly, an ultrasound and iRAI dual‐modality imaging system utilizing a phased array transducer was used to take coregistered two‐dimensional (2D) iRAI signal amplitude images as well as ultrasound B‐mode images, to map the dose deposition with respect to surrounding anatomy in an ex vivo rabbit liver model with a single linac pulse precision. Results: Using a single element transducer, iRAI measurements showed a highly linear relationship between the iRAI signal amplitude and the linac dose per pulse (r 2 = 0.9998) with a repeatability precision of 1% and a dose resolution error <2.5% in a homogenous phantom when compared to GAFchromic film dose measurements. These phantom results were used to develop a calibration curve between the iRAI signal response and the delivered dose per pulse. Subsequently, a normalized depth dose curve was generated that agreed with film measurements with an RMSE of 0.0243, using correction factors to account for deviations in measurement conditions with respect to calibration. Experiments on the ex‐vivo rabbit liver model demonstrated that a 2D iRAI image could be generated successfully from a single linac pulse, which was fused with the B‐mode ultrasound image to provide information about the beam position with respect to surrounding anatomy in real time. Conclusion: This work demonstrates the potential of using iRAI for real‐time deep tissue dosimetry in FLASH‐RT. Our results show that iRAI signals are linear with dose and can accurately map the delivered radiation dose with respect to soft tissue anatomy. With its ability to measure dose for individual linac pulses at any location within surrounding soft tissue while identifying where that dose is being delivered anatomically in real time, iRAI can be an indispensable tool to enable safe and efficient clinical translation of FLASH‐RT.